Experimental evaluation of RC beam grade 30 under dynamic influence of serviceability limit / Rosli Ngah - Ngah, Rosli (2005)
In the design of reinforced concrete structures, serviceability limit must be satisfied to ensure safety. Serviceability refers to control deflection and cracks width at services loads. Subjected to dynamic loading under static and dynamic load, a study has been carried out to make an experimental investigation on reinforced concrete beam grade 30, with respect to the serviceability limits. A total 4 beam has been cast and test under static and dynamic load. 1 000 000, 2 000 000 and 3 000 000 cycle has been used as for 5 Hertz loading. Parameters investigated include deflections, crack widths and crack lengths. It is expected that the cracking at reinforced concrete beam. The maximum crack width that may be considered to be acceptable in a given situation depends on the type of reinforced concrete beam, the environment and the consequences of excessive cracking.